Effect of soaking conditions on properties of Khao Dawk Mali 105 - Ji-u, Phornpan; Inprasit, Chouw (Agriculture and Natural Resources, 2019)
The effects were studied of soaking conditions on the physical properties and water absorption behavior of Khao Dawk Mali 105 (KDML105) paddy. Samples of KDML105 paddy were soaked in water at four temperatures (room temperature (27.8 ± 0.98°C), 30°C, 40°C, 50°C) for 1–12 hr. The soaking conditions (temperature and time) affected the water absorption of KDML105 paddy. However, the soaking temperature had more influence on the water absorption than the soaking time since the water absorption rate of paddy after the first hour increased from 0.117 kg water/hr/kg solids at room temperature of soaking to 0.159 kg water/hr/kg solids at 50°C soaking temperature. The suitable conditions for soaking were 50°C for 9 hr and the resultant moisture content of the paddy was higher than 45% on a dry basis and sufficient for gelatinization and germination of Khao Hang rice. For the same period of soaking, water absorption increased with increasing soaking temperature. The effective water diffusion was influenced by the soaking temperature increasing with temperature from 8.85 × 10-12 m2/s to 1.83 × 10-11 m2/s. An Arrhenius relationship was used to describe the water diffusion dependence on the soaking temperature, and the activation energy for water diffusion was 26.48 kJ/mol. Seven empirical models were developed to explain the hydration behavior of KDML105 paddy. The two-term exponential model produced the best results for goodness-of-fit for any soaking time.